2017
DOI: 10.7150/ijbs.17236
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Proteasome Activity Induces Aggregation of IFIT2 in the Centrosome and Enhances IFIT2-Induced Cell Apoptosis

Abstract: IFN-induced protein with tetratricopeptide repeats 2 (IFIT2), one of the most highly responsive interferon-stimulated genes, inhibits the proliferation and migration of cancer cells and regulates viral replication. IFIT2 has been demonstrated to be a cytoskeleton-associated protein that becomes enriched in the mitotic spindle of cells. However, the molecular mechanisms by which IFIT2 executes biological functions are largely unclear. The findings of this study showed that inhibiting the activation of proteasom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Wang et al have suggested that the long non-coding RNA LINC00161 can sensitize the osteosarcoma cells to cisplatin-induced apoptosis by regulating the miR-645-IFIT2 axis [22]. A recent study has also revealed that the inhibition of proteasome activity blocks the degradation of IFIT2 and promotes the aggregation of IFIT2 in the centrosome, which in turn induces cell apoptosis [8]. Therefore, the contribution of IFIT2 in promotion of cell apoptosis might encompass an anti-tumor mechanism for the translational regulation involving in cancerous transformation and inhibition of tumor colonization, and thus it could be used as a potential target for cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al have suggested that the long non-coding RNA LINC00161 can sensitize the osteosarcoma cells to cisplatin-induced apoptosis by regulating the miR-645-IFIT2 axis [22]. A recent study has also revealed that the inhibition of proteasome activity blocks the degradation of IFIT2 and promotes the aggregation of IFIT2 in the centrosome, which in turn induces cell apoptosis [8]. Therefore, the contribution of IFIT2 in promotion of cell apoptosis might encompass an anti-tumor mechanism for the translational regulation involving in cancerous transformation and inhibition of tumor colonization, and thus it could be used as a potential target for cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…It can inhibit the proliferation and migration of cancer cells and regulate viral replication, exerting an anti-cancer as well as anti-viral effect mediated by IFN [5-8]. The expression of IFIT2 can also promote cell death via apoptosis through a mitochondrial pathway dependent on Bcl2 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, IFIT-family proteins display distinct functions in apoptosis. The negative association of IFIT2 with tumor malignancy is likely due to its pro-apoptotic activity (Stawowczyk et al, 2011;Chen et al, 2017). Ectopic IFIT2 overexpression induced the activation of caspase-3 and disturbed the plasma membrane asymmetry and permeability, which is a basic characteristic feature of apoptosis (Stawowczyk et al, 2011;Lai et al, 2013;Feng et al, 2014).…”
Section: Ifits In Apoptosismentioning
confidence: 99%
“…In addition, IFIT2 was associated with the mediator of IRF3 activation (MITA) and regulated apoptotic cell death via the mitochondrial pathway (Stawowczyk et al, 2011). Inhibition of proteasome-mediated degradation of IFIT2 led to the aggregation of IFIT2 in the perinuclear region and promoted apoptosis (Chen et al, 2017). Derepression of IFIT2 made the cells prone to apoptotic death induced by external stimuli such as chemotherapeutic drugs and serum starvation (Feng et al, 2014;Wang et al, 2016).…”
Section: Ifits In Apoptosismentioning
confidence: 99%
See 1 more Smart Citation